Diflunisal tolerability in transthyretin cardiac amyloidosis: a single center's experience. (3rd July 2018) - Ikram, Asad; Donnelly, Joseph P.; Sperry, Brett W.; Samaras, Christy; Valent, Jason; Hanna, Mazen
Abstract: Objective: Transthyretin (ATTR) amyloidosis is an under-recognized, progressive disease manifesting as cardiomyopathy and/or polyneuropathy. Diflunisal, a nonsteroidal anti-inflammatory drug (NSAID), has demonstrated transthyretin stabilization in vitro and slowing of polyneuropathy progression in the hereditary ATTR subtype (ATTRm). However, the use of diflunisal has only been described in a small cohort of patients with ATTR cardiac amyloidosis (CA). We hypothesized that selected patients with ATTR-CA, both hereditary and wild-type (ATTRwt), would tolerate diflunisal with limited adverse events. Materials and methods: This is a retrospective, longitudinal study of 23 patients with ATTR-CA (10 ATTRm and 13 ATTRwt) diagnosed at the Cleveland Clinic from May 2007 to August 2017 who were treated with diflunisal. Patients were prescribed diflunisal, fully informed of the risks of side effects. Patient characteristics and subsequent adverse events were recorded. Results: The duration of diflunisal therapy ranged from 1–89 months (median 15 months). Average eGFR at diflunisal initiation was 61.9 ± 15.4 mL/min/m 2 . Only one patient had a transient rise in Cr of 0.31 mg/dL. There were no clinically significant bleeding events, despite most of the patients being on anticoagulants or antiplatelet agents. Three of 23 patients (13%) withdrew treatment due to drug side effects (erosive gastritis, epigastric pain and decreased appetite). No patients died or were hospitalized for heart failure. Conclusion: Diflunisal was well-tolerated in both the ATTRm- and ATTRwt-CA populations. Withdrawal due to side effects was related to gastrointestinal complaints, but most patients had no adverse events. Diflunisal can be safely used in a selected group of ATTR-CA patients with appropriate clinical, renal and hematologic monitoring.